Presence of SopE and mode of infection result in increased Salmonella‐containing vacuole damage and cytosolic release during host cell infection by Salmonella enterica. (10th February 2020) - Röder, Jennifer; Hensel, Michael
Abstract: Salmonella enterica serovar Typhimurium (STM) is an invasive, facultative intracellular pathogen that has evolved sophisticated molecular mechanisms to establish an intracellular niche within a specialised vesicular compartment, the Salmonella ‐containing vacuole (SCV). The loss of the SCV and release of STM into the cytosol of infected host cells was observed, and a bimodal intracellular lifestyle of STM in the SCV versus life in the cytosol is currently discussed. We set out to investigate the parameters affecting SCV integrity and cytosolic release. A fluorescent protein‐based cytosolic reporter approach was established to quantify, time‐resolved, and on a single cell level, the release of STM into the cytosol of host cells. We observed that the extent of SCV damage and cytosolic release is highly dependent on experimental conditions such as multiplicity of infection, type of host cell line, and STM strain background. Trigger invasion mediated by the Salmonella Pathogenicity Island 1‐encoded type III secretion system (SPI1‐T3SS) and its effector proteins promoted cytosolic release, whereas cytosolic bacteria were rarely observed if entry was mediated by zipper invasion. Presence of SPI1‐T3SS effector SopE was identified as major factor for damage of the SCV in the early phase after STM invasion and sopE ‐expressing strains showed higher levels of cytosolic release.